The Poetics of Space and Place in Scottish Literature
XXII, 304 p. 17 illus., 14 illus. in color.
Keywords: This book addresses the poetics of space and place in Scottish literature. Focusing chiefly on twentieth- and twenty-first century texts, with acknowledgement of historical and philosophical contexts, the essays address representation, narrative form, the work of the poetic, perception and experience. Major genres and forms are discussed, and authors as diverse as George Mackay Brown, Kathleen Jamie, Ken McLeod and Kei Miller are presented through theoretically informed, historically contextualized close readings. Additionally considering the role of dialect and region in the poetry and fiction of modern Scotland, the volume argues for an appreciation of the cultural diversity of Scottish writers while highlighting the overarching presence of a connection between self and world, subject and place within Scottish literature.